A particular frozen yogurt has 75 cal into ounces how many calories are in 8 ounces of the yogurt

Answers

Answer 1
Answer: I'm guessing you mean 75 calories in 2 ounces. 
In that case... you would do
75 / 2 = 37.5
37.5 x 8 = 300 calories in 8 ounces of yogurt

Hope I helped!

Related Questions

Frank, Mary and Seth shared some sweets in the ratio 4:5:7.Seth got 18 more sweets than Frank. Work out the total number of sweets they shared.
Which event is considered neither likely nor unlikely?A. rolling a number greater than one on a six-sided number cubeB. rolling a 1 on a six-sided number cubeC. getting heads when flipping a coinD. choosing a X, Y, or Z from a bag containing all letters in the alphabet
Simplify (-3)⁴x(7)⁴​
jalil and Victoria are each asked to solve the equation ax – c = bx + d for x. Jalil says it is not possible to isolate x because each x has a different unknown coefficient. Victoria believes there is a solution, and shows Jalil her work:
In rectangle KLMN, KM =6x + 16, and LM =49. find the value of x

Solve. Good luck! Please do not try to google this.(x^2+x-2)/(6x^2-3x) = √(2x) + (3x^2)/(2)

Answers

(x^(2) + x - 2)/(6x^(2) - 3x) = √(2x) + (3x^(2))/(2)
(x^(2) + 2x - x - 2)/(3x(x) - 3x(1)) = (2√(2x))/(2) + (3x^(2))/(2)
(x(x) + x(2) - 1(x) - 1(2))/(3x(x - 1)) = (2√(2x) + 3x^(2))/(2)
(x(x + 2) - 1(x + 2))/(3x(2x - 1)) = (2√(2x) + 3x^(2))/(2)
((x - 1)(x + 2))/(3x(2x - 1)) = (2√(2x) + 3x^(2))/(2)
((x - 1)(x + 2))/(3x(2x - 1)) = (2√(2x) + 3x^(2))/(2)
3x(2x - 1)(2√(2x) + 3x^(2)) = 2(x + 2)(x - 1)
3x(2x(2√(2x) + 3x^(2)) - 1(2√(2x) + 3x^(2)) = 2(x(x - 1) + 2(x - 1))
3x(2x(2√(2x)) + 2x(3x^(2)) - 1(2√(2x)) - 1(3x^(2))) = 2(x(x) - x(1) + 2(x) - 2(1)
3x(4x√(2x) + 6x^(3) - 2√(2x) - 3x^(2)) = 2(x^(2) - x + 2x - 2)
3x(4x√(2x) - 2√(2x) + 6x^(3) - 3x^(2)) = 2(x^(2) + x - 2)
3x(4x√(2x)) - 3x(2√(2x)) + 3x(6x^(3)) - 3x(3x^(2)) = 2(x^(2)) + 2(x) - 2(2)
12x^(2)√(2x) - 6x√(2x) + 18x^(4) - 9x^(3) = 2x^(2) + 2x - 4
12x^(2)√(2x) - 6x√(2x) = -18x^(4) + 9x^(3) + 2x^(2) + 2x - 4
6x√(2x)(2x) - 6x√(2x)(1) = -9x^(3)(2x) - 9x^(3)(-1) + 2(x^(2)) + 2(x) - 2(2)
6x√(2x)(2x - 1) = -9x^(3)(2x - 1) + 2(x^(2) + x - 2)

Final answer:

To solve the given equation, first simplify both sides. Factor the numerator and denominator on the left side, then solve the quadratic equation obtained.

Explanation:

To solve the given equation:

(x^2+x-2)/(6x^2-3x) = √(2x) + (3x^2)/(2)

First, we need to simplify both sides of the equation. By factoring the numerator and denominator of the left side, we get:

x+22x.

Next, we can simplify the equation further by multiplying both sides by 2x. Finally, we solve the quadratic equation obtained by moving all terms to one side:

2x+4.

Therefore, the solution to the given equation is x = -2.

Learn more about Solving Equations here:

brainly.com/question/17595716

#SPJ12

Sorry for all the math questions but I do not understand this at all. someone explain and write the equation for me please?? they are the exact words... doesn't make sense to me:the sum of three times a number (z) and 15 is equal to 21.

Answers

3Z + 15 = 21 equation

1. solution
3Z + 15 = 21
3Z = 21 - 15
3Z = 6   [:3
Z = 2

2 solution
3Z + 15 = 21 [:3
Z + 5 = 7
Z = 7 - 5 = 2

Please help will mark brainliest and 20 points

Answers

Answer:

10 weeks

Step-by-step explanation:

she already has 14

so 5 x 10 = 50

14+50=64

Darryl’s credit card has a minimum monthly payment of 2.51% of the card’s balance. If Darryl currently owes $1,431.72, what is his minimum payment, to the nearest cent? a. $29.95 b. $33.67 c. $2.99 d. $35.94

Answers

1,431.72 x 0.0251 = about 35.9            That makes your answer D

Answer:

d.

$35.94

Step-by-step explanation:

just took the test

Convert 38% into a fraction

Answers

When converting numbers we always put the number over 100, so your answer is 38/100. Now when simplifying the fraction we are going to be utilizing the greatest common factor (GCF) so when we do that the answer we get is 19/50.
I hope this helps! 

For the Best Answer: 8+4Paul needs 4.5 cups of flour and 0.5 cup of brown sugar for his recipe.
Which statement best describes how much of each ingredient Paul needs to measure?

A.Paul should measure exactly 4 cups of flour and 1 cup of brown sugar since that makes a total of 5 cups of ingredients.


B.Paul should measure exactly 4.5 cups of flour and 0.5 cup of brown sugar so that he has enough flour and not too much brown sugar for the recipe.


C.Paul should make it easy and just measure a total of 5 cups of flour and brown sugar since it all gets mixed up in the recipe anyway.

Answers

The answer is B because that's what the recipe calls for that's what he needs to do otherwise it won't turn out right.